The Effect of Shading and Nutrient Addition on the Microphytobenthos, Macrofauna, and Biogeochemical Properties of Intertidal Flat Sediments - Tolhurst, Trevor J.; Chapman, M. G.; Murphy, R. J. (Frontiers in Marine Science, 2020)
Proliferation of urban structures and mangrove forests in estuaries are altering the shading of intertidal sediments. Urbanisation also tends to increase nutrient loads in estuaries, which can have numerous direct and indirect effects on estuarine flora and fauna. Mangrove canopy shades the sediment and provides nutrients to the ecosystem via leaf litter. Microphytobenthos, macrobenthos, sediment erodibility and various biogeochemical properties of sediments have been shown to differ significantly between unshaded intertidal sediment and nearby sediment under a mangrove canopy. This study tested the effects of experimental manipulation of shading and addition of nutrients on the microphytobenthos, macrobenthos, sediment erodibility and selected biogeochemical properties of exposed mudflat next to the seaward edge of a mangrove forest. In the first of two experiments, shading of plots was increased by the addition of black Perspex roofs for comparison with unshaded plots and plots with clear Perspex roofs; the addition of nutrients was done in an orthogonal design. Clear roofs were originally intended as a procedural control, but due to sedimentation on their upper surface caused intermediate levels of shading. Sediment and benthos were sampled after two weeks. Nutrients were omitted in the second experiment, with plots sampled after two weeks or three months. The only effect of nutrients was a small negative effect on chlorophyll a and colloidal carbohydrate. Intermediate shading (clear roofs) consistently increased measures of microphytobenthos biomass (e.g. Fo and chlorophyll a) and biogeochemical properties associated with microphytobenthos such as colloidal carbohydrate. Substantial shading (black roofs) decreased measures of microphytobenthos biomass and microphytobenthos associated biogeochemical properties. Effects on the fauna were much smaller and inconsistent with previous studies, after 3 months assemblages were different under black roofs compared to clear roofs and control plots, with differences primarily driven by changes in the oligochaetes. Natural or anthropogenic changes in shading at larger spatial scales are likely therefore to directly and indirectly change microphytobenthos, sediment properties, macrofauna and hence ecosystem functions; but any flow-on effects to the fauna are difficult to predict without further experiments to understand the indirect and direct responses of fauna to changing microphytobenthos and properties of intertidal sediment.